X-Men - Singer, Bryan; Shuler-Donner, Lauren; Winter, Ralph, 1952-; DeSanto, Tom.; Hayter, David; Stewart, Patrick, 1940-; Jackman, Hugh.; McKellen, Ian.; Berry, Halle; Janssen, Famke, 1964-; Marsden, James, 1973-; Davison, Bruce, 1946-; et al. (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2000)
A war is brewing between those with special powers ("mutants") and the rest of humanity -- and the only ones who can save the humans from certain destruction are a special group of mutants- the "X-Men."
DVD.
English (5.1 surround or Dolby surround) and French (Dolby surround) language soundtracks, with optional subtitles in Spanish ; closed-captioned in English for the hearing impaired.
Patrick Stewart, Hugh Jackman, Ian McKellen, Halle Berry, Famke Janssen, James Marsden, Bruce Davison, Rebecca Romijn-Stamos, Ray Park and Anna Paquin.
Music by Michael Kamen ; director of photography, Newton Thomas Sigel ; editors, Steven Rosenblum, Kevin Stitt, John Wright.
Widescreen format (aspect ratio 2.35:1).
Based on the comic book series of the same name.
Keywords: X-men (Comic strip) -- Film and video adaptations; X-Men (Fictitious characters) -- Drama; Science fiction films; Feature films; Films for the hearing impaired